ON THE VALIDITY OF MEASUREMENT IN KINESIOMETRICS CONTEXT - Prot, Franjo (Annales Kinesiologiae, 2010)
Kinesiometrics is a scientific discipline which deals with problems of measurement in kinesiology, with the development of new theoretical and applied measurement models and with practical procedures in the field of the measurement of behavior relevant to kinesiology. In this document, contribution validity (one of the most important concepts) is systemized and organized from the general bird’s-eye view, taking into the account the psychometric heritage and kinesiometric experience. In the first step we recognize the traditional separation of validities into two major groups, i.e. as validities a priori (in psychometrics aprioristic validities) and validities a posteriori. These two groups are further splitted and divided into several groups and up to four levels, up to the point where concrete data analysis methods and techniques could be recognized for its determination. To be able to recognize most of the problems encountered in grasping validity in its diversity acceptable systematization would be of great help.